COMPARING STUDENTS’ ATTITUDES IN AN ONLINE PEER ASSESSMENT: DOES ANONYMITY MATTER? - Fanya Evelyn Acai; Rina Astuti Purnamaningwulan (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2022)
Peer assessment is a fundamental activity aiming to involve students to participate actively in their own learning processes. In the context of EFL online learning, the peer assessment was conducted in the online mode as well. This study aimed to: 1) compare students’ attitudes in doing an online peer assessment in two different conditions of anonymity, 2) explore students’ perceptions of the anonymous and identifiable online peer assessment. Seventy students of the English language education department in a private university participated in this study. Assigned to two different conditions, i.e anonymous and identifiable online peer assessment, the students were engaged in a Workshop activity, which was an asynchronous Moodle-based online peer assessment. Each student assessed three peers’ works as well as provide feedback comments. A questionnaire with close-ended and open-ended questions was used to investigate the students’ attitudes as well as perceptions of the different peer assessment formats. An independent samples t-test was performed to compare the attitude scores of both groups. The result indicated that students in the anonymous group showed a slightly better attitude compared to those in the identifiable group, yet the difference was not significant (t = 1.164, p > .05). From the questionnaire result, it was also found that the students in the anonymous group had more positive perceptions towards online peer assessment activity. These findings imply that while the anonymous online peer assessment is more favoured by learners, it might not be able to guarantee positive development in students’ overall aspects of attitudes.